2008
DOI: 10.1111/j.1365-2125.2008.03099.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary elimination rate of inhaled 99mTc‐sestamibi radioaerosol is delayed in healthy cigarette smokers

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Very little is known about the physiology of P‐glycoprotein (P‐gp) expression in the lungs. • Ex vivo evidence based on resected lung tissue suggests that pulmonary P‐gp is upregulated by cigarette smoke, but there are no in vivo studies to date. WHAT THIS STUDY ADDS • The novel observation that healthy cigarette smokers have a delayed pulmonary elimination rate of inhaled 99mTc‐sestamibi, a P‐gp substrate, provides for the first time a potential method for quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…They observed that it was significantly slower than the clearance of the hydrophilic radioaerosol, Tcpentetate (25), and hypothesized that the delayed clearance of 99m Tc-sestamibi was due to expression of P-gp in the airway epithelium (26). The clearance rate of inhaled 99m Tc-sestamibi from the lungs was further significantly delayed in healthy smokers versus nonsmokers, and it was hypothesized that this was the result of smoke-induced up-regulation of P-gp (25). …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…They observed that it was significantly slower than the clearance of the hydrophilic radioaerosol, Tcpentetate (25), and hypothesized that the delayed clearance of 99m Tc-sestamibi was due to expression of P-gp in the airway epithelium (26). The clearance rate of inhaled 99m Tc-sestamibi from the lungs was further significantly delayed in healthy smokers versus nonsmokers, and it was hypothesized that this was the result of smoke-induced up-regulation of P-gp (25). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, Ruparelia et al measured the clearance rate of 99m Tc-sestamibi following inhalation as an aerosol from normal lungs in healthy nonsmoking humans (25). They observed that it was significantly slower than the clearance of the hydrophilic radioaerosol, Tcpentetate (25), and hypothesized that the delayed clearance of 99m Tc-sestamibi was due to expression of P-gp in the airway epithelium (26).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations